The role of advanced crisis management in providing relief during an earthquake using the location of vulnerable areas based on the risk matrix (case study: Lahijan city) (Journal of Civil Engineering Researchers, 2022)
In general, crisis management means purposefully pushing the progress of affairs to a controllable routine and expecting things to return to the pre-crisis conditions as soon as possible. In short, crisis management is all actions related to prevention and risk management, organization and management of resources needed in response to crisis. Crisis management is an applied science that, through systematic observation of crises and their analysis, seeks to find tools that can be used to prevent the occurrence of crises or, in case of occurrence, in terms of reducing the effects of the crisis, necessary preparation and rapid relief. and took action to improve the situation. The main purpose of this research is modern crisis management in the probability of an earthquake based on risk matrix by locating vulnerable areas in Lahijan city using AHP, TOPSIS and SWOT analysis.
Keywords: Crisis management; Feasibility study; AHP hierarchical analysis